Dog Flea Ctenocephalides canis (Curtis) (Insecta: Siphonaptera: Pulicidae) - Krista R. Seraydar; Phillip Kaufman (EDIS)
This document provides an overview of the dog flea, Ctenocephalides canis, including its biology, distribution, and medical significance. It details the flea’s life cycle, from egg to adult, and highlights its role as an ectoparasite on various mammalian hosts. The article also discusses the flea’s ability to transmit parasitic worms and cause allergic reactions in pets. Management and prevention strategies for controlling flea infestations are outlined, emphasizing the importance of hygiene and the use of chemical treatments.